Acitretin‐Responsive Ichthyosis in Chanarin–Dorfman Syndrome with a Novel Mutation in the ABHD5/CGI‐58 Gene. Issue 5 (12th June 2013) - Srinivasaraghavan, Rangan; Krishnamurthy, Sriram; Chandar, Rumesh; Cassandrini, Denise; Mahadevan, Subramanian; Bruno, Claudio; Santorelli, Filippo M.
Abstract Chanarin–Dorfman syndrome (CDS) is a rare nonlysosomal neutral lipid storage disorder characterized by congenital ichthyosis, lipid vacuoles in leukocytes (Jordan's anomaly), and hepatomegaly. The authors herein report an 18‐month‐old boy with ichthyosis and hepatomegaly diagnosed with CDS and confirmed to have a novel c.506–3C>G mutation in the ABHD5/CGI‐58 gene. Our case also illustrates that retinoids such as acitretin could be useful in the treatment of skin manifestations in CDS even in the presence of liver derangement.